Advances in 3D bioprinting technology for functional corneal reconstruction and regeneration - Jia, Shuo; Bu, Yashan; Lau, Dzi-Shing Aaron; Lin, Zhizhen; Sun, Tianhao; Lu, Weijia William; Lu, Sheng; Ruan, Changshun; Chan, Cheuk-Hung Jonathan (Frontiers in Bioengineering and Biotechnology, 2023)
Corneal transplantation constitutes one of the major treatments in severe cases of corneal diseases. The lack of cornea donors as well as other limitations of corneal transplantation necessitate the development of artificial corneal substitutes. Biosynthetic cornea model using 3D printing technique is promising to generate artificial corneal structure that can resemble the structure of the native human cornea and is applicable for regenerative medicine. Research on bioprinting artificial cornea has raised interest into the wide range of materials and cells that can be utilized as bioinks for optimal clarity, biocompatibility, and tectonic strength. With continued advances in biomaterials science and printing technology, it is believed that bioprinted cornea will eventually achieve a level of clinical functionality and practicality as to replace donated corneal tissues, with their associated limitations such as limited or unsteady supply, and possible infectious disease transmission. Here, we review the literature on bioprinting strategies, 3D corneal modelling, material options, and cellularization strategies in relation to keratoprosthesis design. The progress, limitations and expectations of recent cases of 3D bioprinting of artifial cornea are discussed. An outlook on the rise of 3D bioprinting in corneal reconstruction and regeneration is provided.